The formal model of information technology for improving the quality of service data flow based on local model of controlled process - Гученко, М. І.; Костенко, П. П.; Славко, О. Г.; Сохін, Н. Л. (Problems of Informatization and Control, 2015)
Made formulation of the problem of creation of information technology to improve quality of servicedata flow based on the local model of the controlled process. Completed development of a formalmodel of information technology